2014
DOI: 10.1039/c3sc53526f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of diarylmethylamines via palladium-catalyzed regioselective arylation of 1,1,3-triaryl-2-azaallyl anions

Abstract: Diarylmethylamines are of great interest due to their prevalence in pharmaceutical chemistry. As a result, new methods for their synthesis are in demand. Herein, we report a versatile protocol for the synthesis of diarylmethylamine derivatives involving palladium-catalyzed arylation of in situ generated 2-azaallyl anion intermediates. The 2-azaallyl anions are generated by reversible deprotonation of readily available aldimine and ketimine precursors. Importantly, the arylated aldimine and ketimine products do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 63 publications
0
32
0
1
Order By: Relevance
“…Substrates reported to date include chromium-activated benzylic amines, 7 diarylmethanes, 8 allylarenes, 9 amides, 10 sulfones, 11 sulfoxides, 12 imines, 13 phosphine oxides 14 and benzylic phosphonates. 15 We have found that van Leeuwen’s NiXantphos 16 (See Scheme 1 for structure) enables a number of these transformations, whereas other ligands are significantly less effective or fail to provide even trace products.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Substrates reported to date include chromium-activated benzylic amines, 7 diarylmethanes, 8 allylarenes, 9 amides, 10 sulfones, 11 sulfoxides, 12 imines, 13 phosphine oxides 14 and benzylic phosphonates. 15 We have found that van Leeuwen’s NiXantphos 16 (See Scheme 1 for structure) enables a number of these transformations, whereas other ligands are significantly less effective or fail to provide even trace products.…”
mentioning
confidence: 99%
“…15 We have found that van Leeuwen’s NiXantphos 16 (See Scheme 1 for structure) enables a number of these transformations, whereas other ligands are significantly less effective or fail to provide even trace products. 8, 12a, 13 The high reactivity of the NiXantphos-based palladium catalysts may be due to the deprotonation of the ligand N–H under basic reaction conditions. 8a Based on these studies, we decided to examine DCCP of sp 2 C–H bonds.…”
mentioning
confidence: 99%
“…We have found that different phosphine ligands are required (Figure 1, ligands L1–L5 ) for the diverse substrate classes and bases we have employed. This method has proven successful for the direct C–H arylation of diarylmethanes ( L1 ), [19] benzylic ketimines ( L1 ), [20] benzyl thioethers, [21] benzylic phosphine oxides ( L2 ), [22] methyl sulfoxides and sulfones ( L3 ), [23] amides ( L3 ), [24] benzylic phosphonates ( L4 ), [25] and allyl benzenes ( L5 ). [26] …”
Section: Resultsmentioning
confidence: 99%
“…A slight increase in AY was observed at 0.05 m (75 % assay yield; Table , entry 4). Buchwald precatalysts, facilitate catalyst generation, often lead to increased activity, and allow a lower ligand loading. Therefore, we employed Buchwald‐type precatalysts 6 and 7 (with L=NiXantphos; Table , entries 5 and 6).…”
Section: Methodsmentioning
confidence: 99%